Ecological distribution and niche segregation of sibling species: the case of bean beetles, Acanthoscelides obtectus Say and A. obvelatus Bridwell - Alvarez, Nadir; Mercier, Lény; Hossaert-McKey, Martine; Contreras-Garduño, Jorge; Kunstler Georges; Aebi, Alexandre; Benrey, Betty (My University, 2006)
1. Molecular techniques have greatly added to the number of known sympatric cryptic species in insects. Ecological differences between these newly distinguished species are little explored, but niches often appear to overlap strongly. These cases are good models for exploring new ideas about species coexistence and community structure.
2. Acanthoscelides obtectus and A. obvelatus are two sister species of bean bruchids, which have been confused until the last decade. One important ecological difference between them has emerged, however: A. obtectus is multivoltine and now distributed worldwide, whereas A. obvelatus is univoltine and restricted to Mesoamerica. Where their ranges overlap, the two species share the same host plants and larvae can sometimes complete development in the same seed.
3. The analysis of 27 622 Mexican individuals of the two species in 2001-2002 and 2002-2003 indicates that their niches overlap, but are differentiated with respect to altitude and the kind of beans (wild vs. domesticated). The principal patterns in their relative abundance in different habitats, and at different seasons, were constant from one year to the next.
4. As sympatry of these species seems to be of recent origin, the observed niche differentiation may not have evolved in response to competition, but could instead be the consequence of physiological differences, evolved independently in each species in allopatry, that pre-adapted them for different altitudes and kinds of resources.
5. The combination of biological and historical factors thus appears to allow these two sibling species to coexist in sympatry, despite their broadly overlapping ecological niches.